Production technology and chromato-mass spectroscopy of the valeriana officinalis tinctures - Yu. I. Korniievskyi; V. M. Odyntsova; V. H. Korniievska; N. V. Kandybei; N. Yu. Bohuslavska (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Underground organs of Valeriana Officinalis are part of multicomponent phytocompositions, which allows them to vary the content and, thus, intensively affect various links of pathological disorders in the body. Despite this, valeriana drug remains poorly understood because of its extraordinary polymorphism.